Reducing Free Fatty Acids in Crude Palm Oil Using Diethylene Glycol and Zinc(II) Chloride Based Deep Eutectic Solvent - Suriyanti, Lieli; Usman, Thamrin; Rahmalia, Winda (Universitas Gadjah Mada, 2024)
Deep eutectic solvents (DES) were prepared by precise combinations of mol fractions of chemical compounds, resulting in a lowered melting point due to hydrogen bonding. This research aimed to elucidate the physicochemical attributes of DES and its effectiveness in mitigating free fatty acid (FFA) levels in crude palm oil (CPO). Zinc(II) chloride (ZnCl2) served as the hydrogen bond acceptor (HBA) while diethylene glycol (DEG) as the hydrogen bond donor (HBD). Characterization included freezing point, density, viscosity, conductivity, and pH determination. At a ZnCl2 mol fraction of 0.30, the resulting DES exhibited homogeneity with transparent liquid properties, featuring a freezing point below −10 °C, density of 1.42 g/mL, viscosity of 1933.40 cP, conductivity of 66.13 µS/cm, and pH 3.42. FTIR spectra confirmed hydrogen bond interactions between HBA and HBD. Applied to CPO at a 1:1 volumetric ratio (DES:CPO), with 2 h of stirring time at 50 °C, FFA content decreased from 4.11 to 0.86%. This research highlights DES as an environmentally sustainable purification agent, significantly reducing FFA levels in unrefined palm oil.